ROBIN HOOD IS THE EMBODIMENT OF FOLK ART AND FOLK HERO - Xudoyberganova Durdona Ismail’s daughter (Western European Studies, 2024)
This article focuses on the time of Robin Hood and the customs that existed during that time. In order to make the topic more clear, let's show the traditions highlighted in the work throughout the article. In addition, information is given on the concept of ballad and when this term entered the language. Moreover article examines the depiction of feudal society and outlaw culture in Robin Hood's time in The Ballad of Robin Hood
Keywords: translator; translation; analysis